An Innovative and Easy Dome Holding Technique for Transdomal Suture in Rhinoplasty. Issue 6 (September 2018) - Seneldir, Sureyya; Durna, Yusuf Muhammed
Abstract : Abstract: Suture tip plasty is one the most used methods in nasal tip surgery. Transdomal suture (TDS) used for this purpose is utilized for providing the dome symmetry, thinning the nasal tip, and enhancing the nasal tip projection and rotation. However, there are not sufficient visual data on what the dome position should be during TDS. In this study, it was aimed to be directive in tip plasty and to define the convenient dome holding technique during TDS. Patients, 510 male and 621 female at the age of 18 to 50 years, who underwent the open technique septorhinoplasty between the years of 2003 to 2015 were included in the authors' study. The length of the patient follow-up varies between 1 and 10 years. Patients, on which the lateral crural strut graft was used and which underwent dome division/vertical dome division in tip surgery, and patients who were diagnosed with the alar cartilage asymmetry and underwent dome excision for any pathological reason to demonstrate the effectiveness of the TDS holding technique. During the TDS, the dome area was administered with 5/0 polydioxanone by being held at an angle close to the cranial in the posterior and the caudal in the anterior with a dentated forceps. In this study according the authors' pre and postoperative conclusions, the authors consider that this is a sufficient visual data on what the dome position should be during TDS by presenting video. Abstract : Supplemental Digital Content is available in the text